"I Control What I Eat and I'm Sensible with What I Eat, Apart from School" – A Qualitative Study of Adolescents' Food Choices and the School Environment. (29th May 2020) - Ryan, David; Holmes, Melvin; Ensaff, Hannah
Abstract: Objectives: Adolescent obesity is a significant issue in the UK, with 36% of 11 to 15 year olds classified as overweight or obese. Schools are seen as a sound setting to address this phenomenon. Mandatory School Food Standards have endeavoured to improve the nutritional profile of school food provision. However students often choose micronutrient poor, energy dense options. This study aimed to explore how and why secondary school students make their food choices within the school environment. Methods: Seven focus group interviews were conducted with students ( n  = 28) aged 13–14 years in a school in Northern England. Development of the focus group schedule was informed by the socio-ecological model and food choice process model. Question topics included school food provision, students' food choices and the role of friends and family in students' food choices. Discussions were audio-recorded, transcribed verbatim and analysed using an inductive thematic approach: an iterative process of reading and re-reading transcripts, coding of nodes and grouping of nodes into unique themes. NVivo12 software was used to facilitate data management. Results: Six initial themes emerged; (1) home environment, (2) food knowledge, (3) food choice factors, (4) food autonomy struggle, (5) social influences and (6) home versus school. Findings suggest that adolescents juxtapose the school and home food environments, in terms of food provision, food choices, as well as food-related rules and customs. Students identified food choices at home as being a structured and clearly defined process, with parents and caregivers acting as nutritional gatekeepers. In contrast, students depicted school food choices as being less straight-forward, determined by factors including social influences and school food choice parameters (e.g., time, queues, cost). Students reported choosing less "healthy" items at school than at home, and justified this by reportedly adopting perceived healthier choices/behaviours at home. Conclusions: Both the school and home environment (in)directly influence adolescents' school food choices. Further research is needed to understand these contrasting environmental influences, and how adolescents manage and integrate their food choice behaviours in different environments. Funding Sources: Research funded by the University of Leeds.